The Favelas of Rio de Janeiro: A study of socio-spatial segregation and racial discrimination - OLAVARRIA BERENGUER, Leticia (Revista Iberoamericana de Estudios de Desarrollo)
Race relations in Brazil are characterized by the coexistence of miscegenation (interracial social contact) and racial discrimination. This paper examines to what extent Brazilian race relations are expressed in the urban space, how they inflect its physical configuration and influence the social processes that take place within it. In this sense, it states that as long as it is considered that the space is subjected to power relations it can be asserted that these dynamics are expressed in the configuration of Brazilian cities, particularly in Rio de Janeiro. Thus, the urban structure of Rio reflects certain level of interracial sociability in terms of residence and the social hyper-inequalities of Brazilian society. In addition, the study of the favelas shows how discourses about race and urban space are interconnected and reinforce racial discrimination.